Efeitos dos exercícios mente-corpo sobre a saúde mental, cognitiva e funcional do idoso - OLIVEIRA, Jhonatta Marcos Torres de (2023)
Objective: An active lifestyle and the practice of mind-body exercises can improve the age-related cognitive decline, aspects of mental health and functional autonomy of the aging population. Method: An integrative literature review was performed on PubMED, Scopus, Science Direct and Cochrane databases. The following descriptors were used: “mind-body therapies”, “mental health”, cognition and aging. Inclusion criteria: a) full text availability; b) older adults as study participants, having as intervention some sort of mind-body exercise or systematic reviews and / or meta-analysis of experimental studies; c) cognition or mental health as outcomes; d) articles published since 2010. Results: Mind-body exercises such as Pilates, Yoga, Tai-chi, Mindfulness and Qigong are suitable for older adults’ specific demands. If practiced regularly, mind-body exercises can prevent declines and improve aspects of mental and cognitive health in aging, contributing to the preserved functional autonomy and independence to perform the daily life activities on aging. Conclusion: Mind-body exercise are safe and effective therapies to maintain and improve mental, cognitive, and physical health of older adults’ population and may be an option to primary health care settings.